How to diagnose amyloidosis. Issue 1 (January 2014) - Mollee, P.; Renaut, P.; Gottlieb, D.; Goodman, H.
Abstract Amyloidosis is a rare but devastating condition caused by deposition of misfolded proteins as aggregates in the extracellular tissues of the body, leading to impairment of organ function. High clinical suspicion is required to facilitate early diagnosis. Correct identification of the causal amyloid protein is absolutely crucial for clinical management in order to avoid misdiagnosis and inappropriate, potentially harmful treatment, to assess prognosis, and to offer genetic counselling if relevant. This review summarises the current evidence on which the diagnosis and subtyping of amyloidosis is based, outlines the limitations of various diagnostic techniques, particularly in an Australian and New Zealand context, and discusses optimal strategies for the diagnostic approach to these patients. Recommendations are provided for when particularly to suspect amyloidosis, what investigations are required, as well as an approach to accurate subtyping of amyloidosis.